(untitled) (The Strategic Review for Southern Africa, 2020)
At the centre of China’s radical economic, social and technological transformation was the statesman Deng Xiaoping. Africa-China relations generally date back to the days of African struggles against colonialism and apartheid with some scholars tracing even earlier contacts between Chinese and Africans. The relations continued after independence and institutionalised into platforms such as Forum on China-Africa Cooperation (FOCAC). Despite the historical ties and platforms such as FOCAC, many African countries failed to emulate China’s successful trajectory from a colony to a successful developmental state and world economic powerhouse. Although having historical and presently good relations with China, Namibia failed to use its relations with China to propel the country to economic greatness. Namibia not only has high levels of poverty, unemployment and inequality, the country has one of the highest records of economic inequality in the whole world. This article provides a descriptive account of the Chinese developmental state and draws possible lessons for Namibia to emulate.